The Role of Women in Lok Baintan Floating Market, South Kalimantan: Implication for Tourism Development - Arisanty, Deasy; Normelani, Ellyn; Putro, Herry Porda Nugroho; Anis, Moh. Zaenal Arifin (Journal of Indonesian Tourism and Development Studies, 2017)
Lok Baintan Floating Market is the tourism destination in South Kalimantan. Trading activity in Lok Baintan become the tourism attraction, which traders in the Floating Market are women using the small boat (jukung). The objective of research is to analyze the role of women in Lok Baintan Floating Market. The study uses fieldwork and qualitative approach. Research data is obtained through interviews with traders in the Floating Market. The research shows that women have the important role in floating market. The role of women is to prepare the merchandise the day before selling until then they sell in the floating market in next day. Merchandise is sold by women in the floating market such as agricultural products, fishery products, handicrafts, traditional cuisine, and traditional cakes. Women get both agricultural product and fishery product from their own land or from other traders. Women make their own craft and then sold in the floating market. Women make both traditional dishes and traditional cake and then sold in the floating market. The presence of women in Lok Baintan has improved the local socio-economics of community. In the perspective of tourism development in floating market, there is still need women community empowerment.Keywords: floating market, tourism destination, women role.